COPI vesicle transport is a common requirement for tube expansion in Drosophila. - Jayaram, S.A.; Senti, K.A.; Tiklová, K.; Tsarouhas, V.; Hemphälä, J.; Samakovlis, C. (PLoS ONE, 2008)
Tube expansion defects like stenoses and atresias cause devastating human diseases. Luminal expansion during organogenesis begins to be elucidated in several systems but we still lack a mechanistic view of the process in many organs. The Drosophila tracheal respiratory system provides an amenable model to study tube size regulation. In the trachea, COPII anterograde transport of luminal proteins is required for extracellular matrix assembly and the concurrent tube expansion.We identified and analyzed Drosophila COPI retrograde transport mutants with narrow tracheal tubes. gammaCOP mutants fail to efficiently secrete luminal components and assemble the luminal chitinous matrix during tracheal tube expansion. Likewise, tube extension is defective in salivary glands, where it also coincides with a failure in the luminal deposition and assembly of a distinct, transient intraluminal matrix. Drosophila gammaCOP colocalizes with cis-Golgi markers and in gammaCOP mutant embryos the ER and Golgi structures are severely disrupted. Analysis of gammaCOP and Sar1 double mutants suggests that bidirectional ER-Golgi traffic maintains the ER and Golgi compartments and is required for secretion and assembly of luminal matrixes during tube expansion.Our results demonstrate the function of COPI components in organ morphogenesis and highlight the common role of apical secretion and assembly of transient organotypic matrices in tube expansion. Intraluminal matrices have been detected in the notochord of ascidians and zebrafish COPI mutants show defects in notochord expansion. Thus, the programmed deposition and growth of distinct luminal molds may provide distending forces during tube expansion in diverse organs.